2019
DOI: 10.1108/ijlma-03-2018-0056
|View full text |Cite
|
Sign up to set email alerts
|

The effect of audit committee attributes on compliance with IAS 24-related party disclosure

Abstract: Purpose This paper aims to investigate the compliance with IAS 24 and possible audit committee attributes that can influence companies in Ghana to disclose related party (RP) information in their annual reports. Design/methodology/approach Different univariate tests and multivariate regressions have been used to examine the hypotheses. The sample includes 120 firm-year observations for the period 2013-2016. Findings The findings of the paper reveal that related party disclosure compliance is influenced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…Regarding the regression analysis results, it is determined that AC meetings, AC reports, prior experience, financial expertise, firm liquidity, profitability and leverage do not have a significant relationship with the compliance level. These results offer supportive evidence for prior research conducted on AC characteristics (Talpur et al, 2018;Agyei-Mensah, 2019a;Mnif and Znaze, 2020;Talpur et al, 2018;Bananuka et al, 2019). Only AC gender distribution plays a driving role in increasing compliance within the sample.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Regarding the regression analysis results, it is determined that AC meetings, AC reports, prior experience, financial expertise, firm liquidity, profitability and leverage do not have a significant relationship with the compliance level. These results offer supportive evidence for prior research conducted on AC characteristics (Talpur et al, 2018;Agyei-Mensah, 2019a;Mnif and Znaze, 2020;Talpur et al, 2018;Bananuka et al, 2019). Only AC gender distribution plays a driving role in increasing compliance within the sample.…”
Section: Discussionsupporting
confidence: 86%
“…Firms of a larger size are argued to have more resources to provide effective monitoring (Ettredge et al, 2011). Moreover, Big 4 is argued to have an incentive to signal that their clients have a higher degree of disclosure compliance with the international standards and an incentive to protect their reputation (Mollik and Bepari, 2014;Agyei-Mensah, 2019a). However, counterintuitively, the Pearson correlation analysis shows there is a negative, significant relationship between usage of Big 4 auditing firms, firm size and IAS 24 disclosure compliance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that there is indeed a significant positive relationship between audit committee independence and the level of compliance with IFRS (Adznan and Nelson 2014;Agyei-Mensah 2019a;Juhmani 2017;Krismiaji 2019;Sellami and Fendri 2017;Mnif and Znazen 2020). However, there are also other studies that do not find any effect of this determinant over the degree of compliance, such as Abdul Abdul Rahman and Hamdan (2017), Agyei-Mensah (2017), Bagudo et al (2018), andAlmaqtari (2019).…”
Section: Audit Committee Independencementioning
confidence: 98%
“…While the audit committee is a committee of the board of directors, it contributes significantly to the efficiency of business supervision and risk management in an organization. In order for this committee to fulfill its responsibilities at the required level, it should be independent as far as possible from administrative pressures and be unbiased (Abdul Rahman and Hamdan 2017;Agyei-Mensah 2019a;Sellami and Fendri 2017). This independence ensures the members of the audit committee are unrelated to financial or personal relationships with the company or its executives, and therefore includes non-executive members (Ishak et al 2017).…”
Section: Audit Committee Independencementioning
confidence: 99%